Identification and control of moulds responsible for black spot spoilage in dry-cured ham. (December 2016) - Alía, Alberto; Andrade, María J.; Rodríguez, Alicia; Reyes-Prieto, Mariana; Bernáldez, Victoria; Córdoba, Juan J.
Abstract: The aims of this work were to identify moulds responsible for black spot spoilage in the drying and cellar stages of dry-cured ham processing and evaluate the effectiveness of preventive actions for controlling this alteration. Four mould strains isolated from spoiled hams were identified by morphological characteristics and the ITS and β-tubulin sequencing. Two of them were Cladosporium oxysporum, one was C. cladosporioides and the remaining one was C. herbarum . These spoiling strains reproduced the black spots on dry-cured ham-based media and ham slices. Additionally, the effect of water activity (aw ) conditions reached throughout dry-cured ham ripening and the activity of the protective culture Penicillium chrysogenum CECT 20922 against the spoiling moulds were evaluated. In the dry-cured ham model system the growth of the Cladosporium strains was minimised when the aw approaches 0.84 or in P. chrysogenum CECT 20922 inoculated dry-cured ham slices. Therefore such combination could be used to avoid the black spot formation in dry-cured ham. Highlights: Moulds responsible for black spots in cured ham were characterised. Cladosporium strains were identified as responsible for black spots spoilage. C. oxysporum reproduced the black spots on dry-cured ham slices. Black spots could be avoided by reducing aw of the hams below 0.84. This alteration could be also avoided by using P. chrysogenum CECT 20922.